2004
DOI: 10.3349/ymj.2004.45.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E Supplementation on Oxidative Stress in Streptozotocin Induced Diabetic Rats: Investigation of Liver and Plasma

Abstract: This experimental study was designed to investigate the effects of vitamin E supplementation, especially on lipid peroxidation and antioxidant status elements 3/4 namely, glutathione (GSH), CuZn superoxide dismutase (CuZn SOD), and glutathione peroxidase (GSH Px), both in blood and liver tissues of streptozotocin (STZ) diabetic rats. The extent to which blood can be used to reflect the oxidative stress of the liver is also investigated. In diabetic rats, plasma lipid peroxide values were not significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 0 publications
7
66
0
1
Order By: Relevance
“…Lipid peroxidation also cause protein damage and inactivation of membrane bound enzymes either through direct attack by free radicals or through chemical modification by its end products which are MDA and 4-hydroxynonenal (4-HNE) [26]. According to our results, lipid peroxidation levels in the liver tissues of diabetic rats were significantly higher compared to controls and these findings are in agreement with the results of other related studies [23,27,28]. This marked increase in the lipid peroxidation rates in diabetic tissues suggests an accumulation of oxygen free radicals which can be due to either increased production and/or decreased elimination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Lipid peroxidation also cause protein damage and inactivation of membrane bound enzymes either through direct attack by free radicals or through chemical modification by its end products which are MDA and 4-hydroxynonenal (4-HNE) [26]. According to our results, lipid peroxidation levels in the liver tissues of diabetic rats were significantly higher compared to controls and these findings are in agreement with the results of other related studies [23,27,28]. This marked increase in the lipid peroxidation rates in diabetic tissues suggests an accumulation of oxygen free radicals which can be due to either increased production and/or decreased elimination.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies proposed that, inhibition of oxidative stress with antioxidants might be an effective strategy for reducing the complications of diabetes. The beneficial effects of antioxidants in the treatment of diabetes have been shown by several investigators [19][20][21][22][23]. Although it is clear that oxidative stress plays a major role in diabetic complications, the molecular mechanisms of the effects of antioxidants especially on antioxidant and detoxification enzymes have not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed Vitamin E playing a key role in controlling hyperglycemia, and the combined antioxidants therapy also considered for control and prevention of diabetic complication. The studies in an animal model have shown supplementation of Vitamin E decreases the hepatic lipid peroxide level in streptozotocin-induced diabetes [11]. However, the increased level of lipid peroxide due to change of antioxidant status in the diabetic rat.…”
Section: Vitamin Ementioning
confidence: 99%
“…Eukaryotic cells are equipped with a variety of primary and secondary defenses against the deleterious effects of oxidative stress. As lethal injury can occur when these defenses are overwhelmed, supplementation with antioxidant vitamins such as vitamins A, E and C may be benefi cial (4). Vitamin E is a hydrophobic antioxidant found in lipoproteins and membranes and can afford primary as well as secondary stage protection.…”
Section: Introductionmentioning
confidence: 99%